Relationship Between High Organ Donation Rates and COVID-19 Vaccination Coverage - Inoue, Yusuke (Frontiers in public health, 2022)
Besides attaining the goal of self-protection, the rollout of vaccination programs also encourages altruistic practices. Therefore, the progress in vaccination against coronavirus disease (COVID-19) in each country may be related to the prevalence of cooperative and altruistic practices in health care. I hypothesized that in countries where organ donation is popular, individuals would exhibit a greater tendency to become vaccinated. I examined the correlation between the level of progress of COVID-19 vaccination and the status of organ donation just before the pandemic in Organization for Economic Co-operation and Development (OECD) countries. Publicly available statistical information on the progress of immunization and organ donation was used. Univariate and multivariate analyses were conducted to examine common drivers of immunization and organ donation. In OECD countries, progress in vaccination was found to be significantly correlated with the status of organ donation in each country. This relationship was stable after the summer (September 1: Pearson's = 0.442, October 1: 0.457, November 1: 0.366). The results of the univariate and multivariate analyses showed that high trust in medical professionals was significantly correlated with both the "progress of vaccinations" and "organ donations." Progress in COVID-19 vaccination and organ donation status for transplantation have similar trends, and both may involve people's trust in medical personnel and public health systems. Similar to the efforts to obtain organ donors, governments around the world need to take further steps to ensure that vaccination programs are supported by people's trust and sense of solidarity.